2017
DOI: 10.1021/acs.energyfuels.7b02584
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Looping Combustion of a Typical Lignite with a CaSO4–CuO Mixed Oxygen Carrier

Abstract: Calcium sulfate (CaSO4) has attracted a great amount of attention as a potential oxygen carrier (OC) to be applied in chemical looping combustion (CLC) due to its high oxygen transfer capacity, wide distribution, and easy accessibility, but its low reactivity and sulfur emission from side reactions of CaSO4 should be well resolved. In this research, the CaSO4–CuO mixed OC was prepared using the template method combined with the sol–gel combustion synthesis (SGCS). Its reaction characteristics with a selected l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 71 publications
3
28
0
Order By: Relevance
“…From the related TG and DTG curves, after dehydration of absorbed water in the CaSO 4 substrate below 200 °C, although there still existed three identifiable weight loss stages during the reaction of YN with the reference CaSO 4 −CuO or CaSO 4 −CaO, similar to single CaSO 4 , the inherent reaction characteristics changed a lot. According to our previous research, 21 with regard to the reduction of reference CaSO 4 −CuO by YN, its first reaction stage occurred at the peak temperature of 432.7 °C, much higher than that of the CaSO 4 −CuO reaction with H 2 , as shown in Figure 3 above, which was mainly attributed to oxidation of the gaseous primary pyrolysis products of YN by doped CuO. The resulting CO 2 was formed at the first distinct CO 2 peak, as shown in Figure 5a.…”
Section: Sample Characterizationmentioning
confidence: 97%
See 4 more Smart Citations
“…From the related TG and DTG curves, after dehydration of absorbed water in the CaSO 4 substrate below 200 °C, although there still existed three identifiable weight loss stages during the reaction of YN with the reference CaSO 4 −CuO or CaSO 4 −CaO, similar to single CaSO 4 , the inherent reaction characteristics changed a lot. According to our previous research, 21 with regard to the reduction of reference CaSO 4 −CuO by YN, its first reaction stage occurred at the peak temperature of 432.7 °C, much higher than that of the CaSO 4 −CuO reaction with H 2 , as shown in Figure 3 above, which was mainly attributed to oxidation of the gaseous primary pyrolysis products of YN by doped CuO. The resulting CO 2 was formed at the first distinct CO 2 peak, as shown in Figure 5a.…”
Section: Sample Characterizationmentioning
confidence: 97%
“…From Figure 2a for the prepared CaSO 4 −CuO reference oxide, from point 1 on SEM in Figure 2a, it could be observed that many agglomerated particles were formed below the microsize, which was mainly determined as CuO by the related composition analysis shown in the corresponding EDX pattern on the right side, while, from the point 2 in Figure 2a, CaSO 4 was observed as a platelike shape, which was consistent with our previous research. 21 The CuO particles were found to encapsulate around the exterior surface of the CaSO 4 substrate. Far different from reference CaSO 4 −CuO, from Figure 2b for prepared CaSO 4 −Ca 2 CuO 3 , in combination of the SEM microstructure on the optionally selected points with the corresponding composition analysis by EDX, little white nanosized grains were found to disperse on the surface, as shown in point 1 across the CaSO 4 −Ca 2 CuO 3 mixed OC, which was mainly ascribed to the trace of separate CuO.…”
Section: Sample Characterizationmentioning
confidence: 98%
See 3 more Smart Citations